Understanding Status of Old Age Homes in India - Dr. Radhika Kapur, (Indian Journal of Social Science and Literature (IJSSL), 2024)
The individuals in old age move to old age homes due to different factors. In old age homes, there are provision of infrastructure, amenities and facilities, which are facilitating in carrying out all types of tasks and activities in a well-ordered manner. The individuals employed are required to be wellequipped in terms of different types of job duties and responsibilities. Furthermore, they are required to augment their information in terms of methodologies and approaches, which are facilitating in generating desired outcomes. The main objective of all the staff members living in old age homes is to promote well-being and goodwill of senior citizens. The senior citizens are overwhelmed by different types of health problems and illnesses. In some cases, they are not ambulatory, hence, it is of utmost significance to make provision of medical and health care facilities. The medical practitioners and health care specialists are required to be well-versed in terms of methods and approaches, which are facilitating in doing well in one’s job duties and generating desired outcomes. As a consequence of carrying out job duties efficiently, individuals will contribute in leading to progression of old age homes. Therefore, old age homes are facilitating in promoting well-being and goodwill of senior citizens. The main concepts that are taken into account in this research paper are, estimating supply of old age homes, measures to be implemented in promoting enrichment of status of old age homes in India and causes enabling senior citizens to live in old age homes.